Complications Following Primary Repair of Non-proximal Hypospadias in Children: A Systematic Review and Meta-Analysis - Wu, Yuhao; Wang, Junke; Zhao, Tianxin; Wei, Yuexin; Han, Lindong; Liu, Xing; Lin, Tao; Wei, Guanghui; Wu, Shengde (Frontiers in Pediatrics, 2020)
Purpose To systematically review the literature on the complications and postoperative outcomes of children with non-proximal hypospadias. Methods Electronic databases including PubMed, EMbase, and Cochrane Library CENTRAL were searched systematically from January 1990 to June 2020 for the literature which reported the postoperative outcomes of patients with non-proximal hypospadias. Non-proximal hypospadias encompassed distal and mid-penile hypospadias. Results We included forty-four studies involving 1,0666 subjects. Urethrocutaneous fistula (UCF) was the most common complication with an incidence of 4.0% (95%CI, 3.1% to 5.0%). Incidence of overall complications was 8.0% (95%CI, 6.3% to 9.8%). Meta regression analysis revealed that length of urethral stent indwelling (Coefficient 0.006; 95%CI, 0.000 to 0.011; p=0.036) and penile dressing (Coefficient 0.010; 95%CI, 0.000 to 0.021; p=0.048) were two risk factors for UCF. Multivariate meta regression analysis did not identify any independent risk factors for UCF. No differences were found between stent and stentless group in non-proximal hypospadias regarding incidences of UCF (OR, 0.589; 95%CI, 0.267 to 1.297), meatal stenosis (OR, 0.880; 95%CI, 0.318 to 2.437), and overall complications (OR, 0.695; 95%CI, 0.403 to 1.199). No differences were found between foreskin preservation and circumcision in terms of complications either. Conclusions UCF is the most common complication following hypospadias repair with an incidence of 4.0%. Independent risk factors for UCF were not identified in current research. Distal hypospadias repair without stent indwelling is not likely to compromise the postoperative outcome. Further studies should be designed to explore the differences between different surgical approaches and the potential risk factors for complications following hypospadias repair.